2011
DOI: 10.1002/tl.432
|View full text |Cite
|
Sign up to set email alerts
|

Using an intersectional approach to deepen collaborative teaching

Abstract: The authors use a case study and the theory of intersectionality to expand strategies for collaborative teaching.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Establishing effective teaching practices is a collective as well as an individual responsibility (Lynch et al, 2014). This entails teachers working from the same set of principles and operating collaboratively for taking responsibility for planning the curriculum and instruction, for ensuring that their teaching is effective, for monitoring student learning and development and for stimulating each other's professional learning (Plinter et al, 2011). In several studies a positive relationship between teacher collaboration, teacher retention and student achievement was found (Goddard et al, 2010).…”
Section: Teacher Collaborationmentioning
confidence: 99%
“…Establishing effective teaching practices is a collective as well as an individual responsibility (Lynch et al, 2014). This entails teachers working from the same set of principles and operating collaboratively for taking responsibility for planning the curriculum and instruction, for ensuring that their teaching is effective, for monitoring student learning and development and for stimulating each other's professional learning (Plinter et al, 2011). In several studies a positive relationship between teacher collaboration, teacher retention and student achievement was found (Goddard et al, 2010).…”
Section: Teacher Collaborationmentioning
confidence: 99%
“…A handful of studies examine effective approaches to teach intersectionality, but many do not deeply engage with embodiment. For example, these include drawing from the distinct biographical experiences of instructors through collaboratively taught courses (Pliner, Iuzzini, and Banks 2011); assigning students to think through ethical dilemmas that draw attention to race, class, and gender (Lee 2012); and playing an “Intersectionopoly” game, which is a variation of a stratified version of the board game Monopoly that further develops and deepens inequalities as the game progresses (Paino et al 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the field of education, Pliner, Iuzzini, and Banks (2011) argued that intersectionality could be an effective tool to improve students' learning experiences in an undergraduate setting. Pliner et al taught a course in which the goal was to determine how intersectionality, used as a collaborative teaching tool between students and faculty, could enrich educational experiences by incorporating a diverse range of identities and perspectives in the learning process.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…They found that using intersectionality was a helpful approach to creating an environment that promoted the scaffolding of learning activities assigned to students throughout the semester to ensure a diverse group experience. For students and professors, intersectionality promoted a reflective, collaborative, engaging educational environment (Pliner et al, 2011). Similarly, Hahn Tapper (2013), executive director for the Center of Transformative Education, used intersectionality as a collaborative tool within a religious educational context between students from warring countries.…”
Section: Conceptual Frameworkmentioning
confidence: 99%